La cultura física en el desarrollo de la psicomotricidad en niños y niñas de educación inicial de la parroquia Ignacio flores de la ciudad de Latacunga en el año 2013. Diseño de una guía de estimulación y desarrollo psicomotriz. - William Gerardo, Chicaiza Chuquitarco (2016)
This work contributed to reveal to Physical Education’s teachers and all people involved in children formal education, the meaning of the psychomotor work, especially in early childhood education, as the concept of Physical Culture, focused on the psychomotor as a new discipline, because this was considered as an extracurricular activity, but with this investigative work, it was projected to work into the educational field, linking these two big areas with a general objective: to develop through a physical and mental approach the individual’s capabilities to expand the different aptitudes and potentials of the subject in all aspects of thought and action (motor, social-affective, intellectual-cognitive) heading to a fully thought movement. In this way, the proposal for an Alternative Guide was raised, such as, instructional games with its own strategies and teaching methodologies to stimulated and develop the psychomotor development during early childhood education. With these considerations the teacher’s role plays a fundamental part in learning-teaching process. It is necessary to the human talent to reach this educational objective, with the achievement by the teacher for this Alternative Guide, the results were very noticeable, as the infant was able to develop and acquire new and different abilities and skills: motor ( walk, run, jump and throw) cognitive (read, understand, reflect, imagine) socio-affective (work in groups, interpersonal relationship, self-confidence). Finally it is necessary to make an invitation teachers can continue to incorporate this guide in their daily activities, by renewing their teaching techniques, forming integral children in all manifestations, this is the principal purpose of this investigation work.